2020
DOI: 10.1111/jgh.15353
|View full text |Cite
|
Sign up to set email alerts
|

A review of non‐alcoholic fatty liver disease in non‐obese and lean individuals

Abstract: Non‐alcoholic fatty liver disease (NAFLD) is one of the most common causes of hepatic disorders. It represents a wide range of chronic liver diseases in patients with no history of significant alcohol consumption, starting with simple steatosis and progressing towards non‐alcoholic steatohepatitis, cirrhosis, and ultimately hepatocellular carcinoma. NAFLD is usually associated with type 2 diabetes mellitus, dyslipidemia, metabolic syndrome, and obesity. This disease has mostly been studied in obese individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 145 publications
0
49
0
2
Order By: Relevance
“…Fifth, we did not have dietary data available. Sixth, several NAFLD-associated SNPs, such as rs738409, a single variant in the patatin-like phospholipase domain-containing protein 3, rs12447924 and rs12597002, cholesteryl ester transfer protein, rs58542926 C, a single nucleotide polymorphism in transmembrane 6 superfamily member 2, rs368234815 TT, the interferon lambda 4, and deficiency of the phosphatidylethanolamine N-methyltransferase [ 49 51 ]. Further investigation of SNPs in future studies will clarify the pathogenesis of NAFLD in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we did not have dietary data available. Sixth, several NAFLD-associated SNPs, such as rs738409, a single variant in the patatin-like phospholipase domain-containing protein 3, rs12447924 and rs12597002, cholesteryl ester transfer protein, rs58542926 C, a single nucleotide polymorphism in transmembrane 6 superfamily member 2, rs368234815 TT, the interferon lambda 4, and deficiency of the phosphatidylethanolamine N-methyltransferase [ 49 51 ]. Further investigation of SNPs in future studies will clarify the pathogenesis of NAFLD in the Japanese population.…”
Section: Discussionmentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD), previously thought to predominantly affect obese individuals, 1 has also been shown to occur in subjects who have a relatively normal body mass index (BMI), a condition referred to as non-obese or lean NAFLD, 2 and is occult and therefore easily ignored in clinical examinations. 3 Studies have reported that the incidence rate of NAFLD in non-obese population is 7–20% in the West and 5–26% in the East, 4 however, current studies on NAFLD are mainly focused on obese patients, and there is a lack of research on non-obese patients, the clinical characters and the risk factors of non-obese NAFLD remain poorly defined, sexual dimorphism, advanced age or postmenopausal status, and serum levels of lipid profile and blood glucose levels may be involved. 5 Considering the body figures are different between the Eastern and the western, this paper takes BMI ≥25 kg/m 2 as the definition of obesity according to the recommendation of World Health Organization for the Eastern, 6 the clinical characteristics between obese and non-obese patients with NAFLD were compared and the difference in the risk factors for NAFLD between non-obese male and female patients were also analyzed, the aim is to provide better understandings for non-obese NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Correct dietary habits are important for the regulation of cell membrane in the liver, considered an organ leader in maintaining lipid balance. The combination of diet and physical activity has been considered effective in the prevention of NAFLD [139], so that, clinical studies have demonstrated that both the aerobic and a resistance exercise program physical activity, alone or combined, are capable of reducing NAFLD scores [140,141].…”
Section: Nafld and Lifestyle Interventionsmentioning
confidence: 99%